Analysis of the Stages of Reforming the Tourism Industry Uzbekistan - Khasanova Jamilya Nizamitdinovna; Narzullaeva Durdona (Researchparks Publishing, 2021)
Currently, Uzbekistan has launched a process of cardinal reform of the tourism industry. Its goal is to transform tourism into a strategic direction for the development of the national economy, which will ensure its diversification and accelerated development of the regions. In order to increase the efficiency of the ongoing reforms and a radical increase in foreign citizens entering the republic, by solving the existing problems of the tourism infrastructure, improving the quality of services provided and actively promoting the national tourism product in world markets, strengthening the human resources of the tourism industry, as well as in accordance with the main directions of the Concept development of the tourism sector in the Republic of Uzbekistan in 2019–2025, the necessary measures are being taken.